A HALA / gelma-exosome bioadhesive for SMILE lens transplantation

CN122912169APending Publication Date: 2026-10-16EYE & ENT HOSPITAL SHANGHAI MEDICAL SCHOOL FUDAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611020377.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但其体积小、厚度薄因此缝合困难,同时由于缺乏上皮层,需要角膜周边健康的角膜上皮细胞沿着角膜创面增殖、铺展最终形成连续角膜上皮层,此过程可能导致感染、基质溶解或移植失败,因此需要寻找一个免缝合的替代方案

Benefits of technology

[0023] The HALA/GelMA-exosome biogel provided by this invention, which modifies HA with thioctic acid (LA) to construct a photocrosslinked biogel carrier (HALA), has good optical transparency, adhesion strength, and controllable swelling behavior. After loading exosomes onto the HALA/GelMA biogel, the corneal epithelial repair speed is enhanced based on the properties of HALA/GelMA biogel, and the corneal transparency is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912169A_ABST
    Figure CN122912169A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of medicine preparation, and provides a HALA / GelMA-exosome biological glue and a preparation method thereof.The HALA / GelMA-exosome biological glue has good adhesion, high transparency, anti-swelling characteristics and anti-inflammatory effect.The biological glue has the advantages of simple preparation process, mild conditions, scalable production, wide raw material sources, no toxic side effects, and has extremely high clinical application value and industrialization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of pharmaceutical preparation technology, and in particular to a HALA / GelMA-exosome bioglue for SMILE lens implantation, its preparation method, and its application. Background Technology

[0002] The cornea is a transparent tissue located at the front of the eyeball, and its integrity and transparency are crucial for maintaining normal visual function. Thinning or defects of the cornea can lead to visual impairment, and in severe cases, even blindness. In recent years, corneal stromal lenses obtained through femtosecond laser small incision lenticule extraction (SMILE) have become a popular graft for treating corneal thinning and corneal defects secondary to various corneal diseases due to their excellent optical transparency, low immunogenicity, and reduced dependence on donor corneas. However, their small size and thinness make suturing difficult. Furthermore, the lack of an epithelial layer necessitates the proliferation and spreading of healthy corneal epithelial cells from the periphery along the corneal wound to eventually form a continuous corneal epithelial layer. This process can lead to infection, stromal dissolution, or transplant failure. Therefore, a sutureless alternative is needed.

[0003] Among the current adhesives, cyanoacrylate adhesives can bond quickly and have high strength, but they cause inflammatory reactions; fibrin adhesives have good biocompatibility, but their adhesion strength is insufficient and they cannot withstand the dynamic mechanical environment of the ocular surface. In addition, most bioadhesives exhibit uncontrollable swelling behavior in the tear environment, leading to tissue compression, morphological deformation or decreased adhesion performance, and their optical transparency is also difficult to meet the requirements of corneal repair. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a HALA / GelMA bio-adhesive loaded with exosomes, its preparation method, and its applications. This bio-adhesive adhesive possesses excellent interfacial adhesion, moderate swelling properties, and high transparency, and can improve epithelial repair and inflammation suppression after lens transplantation, demonstrating promising application prospects.

[0005] It has great application value in treating various corneal diseases, such as diverse corneal defects and keratoconus.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] In a first aspect, the present invention provides a method for preparing HALA / GelMA-exosome biogel, characterized by comprising the following steps:

[0008] S1. Mix thioctic acid-modified hyaluronic acid and methacrylamide gelatin evenly to obtain a mixture HALA / GelMA;

[0009] S2. Mix the HALA / GelMA mixture with exosomes and vortex to obtain the HALA / GelMA-Exo biogel precursor. Expose it to light to react and obtain the HALA / GelMA-exosome biogel.

[0010] The exosomes are derived from human umbilical cord mesenchymal stem cells;

[0011] The HALA / GelMA biogel and exosomes are mixed in a volume ratio of 1:1.

[0012] The wavelength of the light is 365 nm; the reaction time is 4-5 min.

[0013] Furthermore, in the preparation method of the HALA / GelMA-exosome biogel, the concentration of thioctic acid-modified hyaluronic acid in the mixture is 20-30 g / L.

[0014] Furthermore, the preparation method of the lipoic acid modified hyaluronic acid includes the following steps:

[0015] S1. Dissolve lipoic acid in N,N-dimethylformamide at a mass concentration of 20 wt%. After dissolution, add N,N'-carbonylimidazolium and stir for 1 hour to obtain lipoic acid imidazolium ester.

[0016] S2. Hyaluronic acid was dissolved in formamide at a mass concentration of 5 wt%, heated and stirred, cooled after dissolution, and the catalyst and thioctic acid imidazole ester were added and mixed. After the reaction was completed, the pH was adjusted to neutral, dialyzed to remove impurities and dried to obtain thioctic acid modified hyaluronic acid.

[0017] Furthermore, in S1, the molar ratio of N,N'-carbonyl imidazole to lipoic acid is 1:1; in S2, the molar ratio of hyaluronic acid: lipoic acid imidazole ester: catalyst is 1:1-3:1, and the catalyst is 4-dimethylaminopyridine.

[0018] Secondly, the present invention provides a HALA / GelMA-exosome biogel prepared by the preparation method described above.

[0019] Thirdly, the present invention provides the application of HALA / GelMA-exosome bioglue in the preparation of lens implantation adhesive.

[0020] Lenticules are natural corneal stroma tissue, lacking an epithelial layer. The epithelial layer is the most important physical and immune barrier of the cornea. After lenticule implantation, rapid migration of host epithelial cells is necessary for re-epithelialization; otherwise, infection or transplantation failure may occur. Simultaneously, the surgery is accompanied by an inflammatory response, which, if uncontrolled, can cause corneal edema and affect visual recovery. Therefore, in lenticule transplantation surgery, it is necessary to improve the adhesive to better meet the biological requirements of promoting epithelialization and reducing inflammation, thus complementing the natural lenticule.

[0021] This bioadhesive has unique swelling properties—it swells moderately in water and exhibits anti-swelling behavior in tear environments, thereby maintaining adhesion stability and preventing tissue compression and morphological deformation.

[0022] Compared with the prior art, the HALA / GelMA-exosome biogel of the present invention has the following advantages:

[0023] The HALA / GelMA-exosome biogel provided by this invention, which modifies HA with thioctic acid (LA) to construct a photocrosslinked biogel carrier (HALA), has good optical transparency, adhesion strength, and controllable swelling behavior. After loading exosomes onto the HALA / GelMA biogel, the corneal epithelial repair speed is enhanced based on the properties of HALA / GelMA biogel, and the corneal transparency is significantly improved. Attached Figure Description

[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0025] Figure 1 Transmittance spectra of bio-adhesives in each group;

[0026] Figure 2 The swelling performance of each group of bio-adhesives was tested. Figure A is a macroscopic visualization of the swelling behavior of each group of bio-adhesives in STF, Figure B is a swelling rate test of each group of bio-adhesives after soaking in STF for 48 hours, Figure C is a macroscopic visualization of the swelling behavior of each group of bio-adhesives in water, and Figure D is a swelling rate test of each group of bio-adhesives after soaking in water for 48 hours.

[0027] Figure 3 Figure A shows the overlap shear curve test results for each group of bio-adhesives, Figure B shows the adhesion strength test results for each group of bio-adhesives, Figure C shows the adhesion strength test results for each group of bio-adhesives after soaking in STF for 48 hours, and Figure D shows the adhesion strength test results for each group of bio-adhesives after soaking in water for 48 hours.

[0028] Figure 4In vivo evaluation images of corneal stromal lenticule implantation in a rabbit corneal defect model. Figure A shows the surgical procedure; Figure B shows immediate postoperative slit-lamp and anterior segment optical coherence tomography (OCT) images, from left to right: slit-lamp diffuse illumination, narrow slit illumination, and anterior segment OCT image (scale bar: 500 μm); Figure C shows representative slit-lamp photographs and anterior segment OCT images at 4 weeks postoperatively, from left to right: slit-lamp diffuse illumination, narrow slit illumination, fluorescein staining, and anterior segment OCT image; Figure D shows HE staining images of the central corneal region in each group at 4 weeks postoperatively; Figures E and F show the immunofluorescence detection results of IL-6 in corneal tissue at 4 weeks postoperatively, with Figure E representing the HG group and Figure F representing the H-G+Exo group (scale bar: 100 μm). μm; Figure G is a schematic diagram of the relative fluorescence intensity of IL-6, *p<0.05, **p<0.01 vs. HG group; Figure H is a schematic diagram of the stromal lenticule adhesion rate over time, Figure I is a schematic diagram of the corneal epithelial defect healing rate over time, Figure J is a schematic diagram of the corneal opacity score over time, *p<0.05, **p<0.01, ***p<0.01 vs. control group; #p<0.05, ##p<0.01, ###p<0.001 vs. HG group, where HG group is the HALA-GelMA-2%-2% group, and H-G+Exo group is the HALA-GelMA-2%-2%+Exo group. Detailed Implementation

[0029] To facilitate understanding of the present invention, a more comprehensive description of the invention will be provided below in conjunction with specific embodiments. Preferred embodiments of the invention are given in the specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the present invention.

[0030] The order in which the embodiments are described below is not intended to limit the preferred order of the embodiments. Furthermore, in the description of this application, the term "comprising" means "including but not limited to". Various embodiments of the invention may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a rigid limitation on the scope of the invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Additionally, whenever a numerical range is indicated herein, it means including any referenced number (fraction or integer) within the indicated range.

[0031] The following specific embodiments further illustrate the HALA / GelMA-Exo bioadhesive adhesive of the present invention, its preparation method, and its application. This section further illustrates the content of the present invention with reference to specific embodiments, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in the art.

[0032] Example 1: Preparation of Modified Hyaluronic Acid

[0033] 1.1 Preparation of modified hyaluronic acid

[0034] S1. Dissolve 0.62 g of lipoic acid (LA) in 3 mL of N,N-dimethylformamide (DMF) to prepare a 20 wt% solution. After complete dissolution, add 0.487 g of N,N'-carbonylimidazole (CDI) and stir at room temperature for 1 hour to fully activate the carboxyl group of lipoic acid, yielding solution A.

[0035] S2 dissolved 1.9 g of hyaluronic acid (HA) in 38 mL of DMF and stirred at 95 °C for 1 h to prepare a 5 wt% solution. After the HA was completely dissolved, the resulting product was cooled to room temperature, and then 0.62 g of 4-dimethylaminopyridine (DMAP) was added as a catalyst to react and obtain solution B.

[0036] S3 mixes solution A and solution B, and the resulting mixture is stirred at room temperature for 4 hours, then neutralized to neutral with potassium dihydrogen phosphate solution;

[0037] S4 purified the neutralized mixture by dialysis using an MD34 dialysis bag with a molecular weight cutoff of 7000 kDa. Dialysis was performed in the dark for 72 hours, with the dialysis medium changed every 6 hours. The mixture was then freeze-dried to obtain the final product HALA.

[0038] 1.2 Characterization of modified hyaluronic acid

[0039] The FT-IR spectra of raw material HA, LA, and product HALA were recorded using a Fourier transform infrared spectrometer equipped with an attenuated total reflectance (ATR) accessory. The spectral acquisition parameters were: 16 scans and a spectral resolution of 4 cm⁻¹. -1 Wavenumber range 400–4000 cm⁻¹ -1 The results showed that the wavelength of HALA was at 1724 cm⁻¹. -1 There exists a C=O stretching vibration with a wavelength of 1240 cm. -1The presence of COC stretching vibrations indicates that HA and LA underwent an esterification reaction, forming ester bonds. These characteristic peaks demonstrate the successful preparation of HALA.

[0040] Example 2 Synthesis of GelMA

[0041] S1. Add 2 g of gelatin to a 250 mL single-necked flask, followed by 20 mL of 0.01 mol / L phosphate-buffered saline (PBS). Heat and stir at 60 °C using a magnetic stirrer with a constant temperature until the gelatin is completely dissolved.

[0042] S2: Add 0.1 mL of methacrylic anhydride (MA) dropwise using a pipette, and stir magnetically at 60 °C for 2 hours. After the reaction is complete, add 80 mL of preheated 60 °C PBS to terminate the reaction.

[0043] S3 was stirred for another 15 minutes to terminate the reaction. Dialysis was performed in deionized water for 3 days using a dialysis bag with a molecular weight cutoff of 7 kDa. The dialyzed solution was filtered through filter paper, then freeze-dried and stored at 4 °C.

[0044] (4) The FT-IR spectra of the samples were recorded using a Fourier transform infrared spectrometer equipped with an attenuated total reflectance (ATR) attachment. Suitable sheet samples for characterization were prepared by pressing them firmly against a sample holder. The sample test surface was placed in close contact with the infrared transmission crystal of the ATR attachment. A germanium (Ge) crystal was used with air as the blank background. The spectral acquisition parameters were: 16 scans, spectral resolution 4 cm⁻¹. -1 Wavenumber range 400–4000 cm⁻¹ -1 In the FT-IR spectrum of GelMA, at 1655 cm⁻¹ -1 A characteristic peak of the amide bond was observed at 3325 cm⁻¹. -1 The peak at that point is attributed to the NH stretching vibration, which corresponds to the amide group and amino structure in the GelMA molecule, indicating that the sample contains the characteristic structure of gelatin methacryloyl (GelMA).

[0045] Example 3: Extraction of exosomes

[0046] Human umbilical cord mesenchymal stem cells (passages 3-5) were cultured, and conditioned medium was collected every other day. The collected medium was pooled into 50 mL centrifuge tubes and subjected to differential ultracentrifugation at 4 °C. The separation process included the following sequential centrifugation steps: centrifugation at 300 × g for 10 min to remove cells, centrifugation at 3,000 × g for 10 min to remove dead cells, centrifugation at 10,000 × g for 60 min to remove cell debris, and finally centrifugation at 120,000 × g for 120 min to precipitate exosomes. The purified exosomes were resuspended in 50 μL of sterile PBS, yielding an exosome particle concentration of 3.65 × 10⁻⁶.10 particles / mL, stored at -80 ℃ for later use. The method for exosome extraction and characterization has been described by Wei et al. in Journal of Nanobiotechnology, 2025, 23:321 (DOI:10.1186 / s12951-025-03366-2).

[0047] Example 4: Preparation of HALA / GelMA biogel

[0048] An aqueous solution containing 2% HALA + 2% GelMA by volume was prepared according to the method in Examples 1-2.

[0049] Comparative Example 1: An aqueous solution containing 1% HALA + 3% GelMA by volume was prepared according to the methods of Examples 1-2;

[0050] Comparative Example 2: An aqueous solution containing 3% HALA + 1% GelMA by volume was prepared according to the method of Examples 1-2;

[0051] Comparative Example 3: An aqueous solution containing 4% GelMA by volume was prepared according to the method of Examples 1-2.

[0052] The above aqueous solution was placed in a mold and exposed to ultraviolet light (365 nm, 250 W) for 5 minutes to form a gel, thus obtaining HALA / GelMA-2%-2% biogel, HALA / GelMA-1%-3% biogel, HALA / GelMA-3%-1% biogel and GelMA-4% biogel.

[0053] Example 5: Transparency Detection of HALA / GelMA Bio-adhesive

[0054] The light transmittance of each group of bio-adhesives was measured using a UV-Vis spectrophotometer (V-750 Japanese spectrophotometer). The bio-adhesive precursor solution was uniformly coated onto the inner surface of a quartz glass slide, with an empty quartz glass slide serving as a control. After UV curing, the visible light transmittance spectra in the wavelength range of 400–900 nm were recorded. The results showed that the HG bio-adhesive exhibited high transmittance in the visible spectral range (400 = 900 nm). The GelMA-4% group had the lowest transmittance, indicating significant light scattering and opacity. Compared to the GelMA-4% group, the introduction of HALA significantly improved the transparency of the bio-adhesive adhesive. HALA-GelMA-2%-2% and HALA / GelMA-3%-1% both showed transmittance above 90% across the entire wavelength range, demonstrating excellent optical transparency (e.g., ...). Figure 1 (As shown)

[0055] Example 6: Detection of HALA / GelMA swelling behavior

[0056] Anti-swelling behavior, also known as negative swelling or deswelling response, is a type of environmental stimulus-responsive specific deformation. Specifically, ion-responsive anti-swelling gels, after swelling in a low-ion water environment, undergo a unique deformation process when the ionic strength or osmotic pressure of the external environment changes. This process restructures the osmotic pressure and intermolecular forces within and outside the network, causing the polymer chains to spontaneously curl up and the network pores to drain water. The entire structure transforms from an expanded state to a controlled-volume shrinkage state. This characteristic allows the gel to transition from a swollen state to a uniformly contracted state within a physiological environment, enabling it to actively adhere to the host eye tissue, stabilize interfacial adhesion, and avoid tissue compression and implant displacement problems caused by traditional swelling.

[0057] The swelling behavior of biogels was monitored in simulated tear fluid (STF preparation method: 670 mg NaCl, 200 mg NaHCO3, 138 mg KCl, 8 mg CaCl2·2H2O, and 5 mg MgCl2 dissolved in 100 mL deionized water) and in deionized water alone. Three groups were designed: HALA / GelMA-1%-3%, HALA-GelMA-2%-2%, and HALA / GelMA-3%-1% solutions, with a GelMA-4% solution as a control group. After UV curing, biogel samples were collected and immersed in simulated tear fluid at room temperature for swelling observation and measurement. The initial mass (m0) and the mass (mt) of each biogel at preset time intervals (12h, 24h, 48h) were accurately recorded. The swelling rate was calculated using the following formula:

[0058] Swelling rate (%) = S

[0059] At 0 hours, all biogels had an initial swelling ratio of 100%. As the experiment progressed, the swelling ratio of GelMA-4% biogel continuously increased in both STF and water. Figure 2 (Image AD in the middle). Similarly, all biogels swelled significantly in water (…). Figure 2 (See Figure AB in the middle). However, conversely, with the increase of HA-LA content, the swelling ratio in STF after 48 hours decreased from 100% to below 70% ( Figure 2 Figure C shows that significant anti-swelling behavior occurred in STF. The results indicate that the introduction of HA-LA gave the HALA / GelMA bioglue physiologically responsive anti-swelling properties, allowing the bioglue to change from swelling to controlled shrinkage in the physiological tear environment.

[0060] Example 7: HALA / GelMA Adhesion Strength Test

[0061] A 4% (w / v) bio-adhesive solution was uniformly coated onto designated areas (2.5 cm × 1.0 cm) of two clean glass slides, which were then gently clamped together. After photocrosslinking under 365 nm UV light irradiation, an lap shear test was performed using an electronic universal tensile testing machine at a tensile rate of 50 mm / min. After UV curing, the tensile rate was set to 50 mm / min during testing. The force-displacement curves were recorded, and the adhesive strength of the bio-adhesive was calculated using the adhesion strength formula.

[0062] The formula is: σ = F / A, where σ represents the adhesion strength in kPa, F represents the maximum force required to pull the glass sheet apart in N, and A is the area of ​​the adhesive coating in cm². 2 .

[0063] Figure 3 Figure A shows the force-displacement curves of the bio-adhesive overlap shear test for each group. The test results show that the peak force of the GelMA-4% curve is the lowest. The peak forces of the HALA / GelMA-2%-2% and HALA / GelMA-3%-1% groups are significantly higher, the area enclosed under the curve is larger, and the displacement before fracture is longer, indicating that the introduction of an appropriate amount of HALA can significantly improve the maximum adhesion of the hydrogel.

[0064] With increasing HALA content, the adhesive strength of the bio-adhesives showed a significant upward trend. The control group, GelMA-4% bio-adhesive, showed the lowest adhesive strength at 15.5 kPa, while the HALA-GelMA-2%-2% and HALA / GelMA-3%-1% bio-adhesives achieved the highest adhesive strengths of 42 kPa and 53 kPa, respectively, approximately three times higher than the control group. Figure 3 As shown in Figure B). The adhesion strength of the photocured bio-adhesive was tested after immersion in STF and water for 48 hours. Figure 3 (Figures C and D). The results showed that the adhesion strengths after soaking in STF were 59 kPa for HALA / GelMA-3%-1%, 49 kPa for HALA-GelMA-2%-2%, and 24 kPa for HALA / GelMA-1%-3%. The adhesion strengths in water were 41.3 kPa for HALA / GelMA-3%-1%, 36 kPa for HALA-GelMA-2%-2%, and 10.5 kPa for HALA / GelMA-1%-3%, indicating that simulating ocular surface conditions was more conducive to maintaining the adhesion of the bio-adhesive. Therefore, the HALA-GelMA-2%-2% group was selected to prepare the bio-adhesive loaded with exosomes in the following section.

[0065] Example 8: Preparation of HALA / GelMA-exosome bioglue and its functional testing in promoting corneal lenticule transplantation

[0066] 8.1 Preparation of HALA / GelMA-Exosome Biogel

[0067] An aqueous solution of 4% HALA + 4% GelMA prepared according to the method in Example 4 was mixed with exosomes at a volume ratio of 1:1 to obtain an exosome solution of 2% HALA + 2% GelMA. The solution was vortexed appropriately and exposed to ultraviolet light (365 nm, 250 W) for 5 minutes to form a gel, thus obtaining HALA / GelMA-exosome biogel.

[0068] 8.2 Functional testing of HALA / GelMA-Exo in lenticule transplantation

[0069] The treatment effect was evaluated using a rabbit corneal defect model. The specific procedures were as follows: The ctrl group did not have a lens implanted; the other three groups received the following solutions: GelMA group received 4% GelMA solution, HG group received 2%-2% HALA-GelMA solution, and H-G+Exo group received HALA / GelMA-exosome bio-adhesive precursor solution. Lenses were then implanted and subjected to 5 minutes of UV irradiation to achieve adhesion. The experimental procedure is as follows: Figure 4 As shown in Figure A, after complete gelation, all experimental groups achieved successful adhesion, and the lenses were firmly bonded to the matrix bed. Figure 4 (Figure B). No significant adverse reactions were observed in the rabbit eyes postoperatively. Following lenticule implantation, the corneal defect was closely monitored for 4 weeks, with photographs taken at week 4. Results are as follows. Figure 4 As shown in Figure C. Statistical results indicate that the in vivo retention stability of the lenticules repaired in the GelMA group was poor. The lenticule retention rate rapidly decreased to 44% on postoperative day 2, dropped to 33% at 1 week, and was only 11% at 2 weeks, with complete detachment by 4 weeks. In contrast, the lenticules repaired in the H-G+Exo group maintained a 100% retention rate throughout the entire experimental observation period; the HG group experienced 20% lenticule detachment at 2 weeks postoperatively, and no further detachment occurred thereafter (results are shown in Figure C). Figure 4 (As shown in Figure H). Meanwhile, the corneal epithelial repair efficiency and corneal transparency recovery effect of the H-G+Exo group were superior to those of the HG group and the GelMA group (…). Figure 4 (Figure I-J).

[0070] To further verify the repair effect and local inflammatory response of corneal defects in each group, corneal tissue was collected from rabbit eyes, and tissue sections were prepared for HE staining and immunofluorescence staining. Interleukin-6 (IL-6) primary antibody was used to incubate the sections overnight at 4 ℃; after thorough washing, the corresponding secondary antibody was added for incubation, and finally, DAPI staining was used for nuclear counterstaining and mounting. HE staining results of corneal tissue 4 weeks post-operation showed that: in the H-G+Exo group, the repaired lenticule remained stably at the corneal defect site; in the HG group, most experimental rabbit eyes retained the repaired lenticule, with only a few samples experiencing lenticule detachment; in the GelMA group, no repaired lenticule remained. Figure 4 (Figure D). Immunofluorescence assay results showed that, compared with the H-G+Exo group, the IL-6 expression level in the corneal defect tissue of the HG group was significantly increased, and the local inflammatory response was more significant. Figure 4 (Figure E-G).

[0071] It is understood that the technical features of the above embodiments can be combined arbitrarily. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0072] The above are merely preferred embodiments of this application, and only specifically describe the technical principles of this application. These descriptions are only for explaining the principles of this application and should not be construed as limiting the scope of protection of this application in any way. Based on this explanation, any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application, as well as other specific embodiments of this application that can be conceived by those skilled in the art without creative effort, should be included within the scope of protection of this application.

Claims

1. A method for preparing HALA / GelMA-exosome biogel, characterized in that, Includes the following steps: S1. Mix thioctic acid-modified hyaluronic acid and methacrylamide gelatin evenly to obtain a mixture HALA / GelMA; S2. Mix the HALA / GelMA mixture with exosomes and vortex to obtain the HALA / GelMA-Exo biogel precursor. Expose it to light to react and obtain the HALA / GelMA-exosome biogel. The exosomes are derived from human umbilical cord mesenchymal stem cells; The mixing ratio of the HALA / GelMA mixture and exosomes is 1:1 by volume. The wavelength of the light is 365 nm; the reaction time is 4-5 min.

2. The preparation method of HALA / GelMA-exosome biogel as described in claim 1, characterized in that, The concentration of lipoic acid-modified hyaluronic acid in the mixture is 20-30 g / L.

3. The preparation method according to claim 1, characterized in that, The preparation method of lipoic acid modified hyaluronic acid includes the following steps: S1. Dissolve lipoic acid in N,N-dimethylformamide at a mass concentration of 20 wt%. After dissolution, add N,N'-carbonylimidazolium and stir for 1 hour to obtain lipoic acid imidazolium ester. S2. Hyaluronic acid was dissolved in formamide at a mass concentration of 5 wt%, heated and stirred, cooled after dissolution, and the catalyst and imidazole ester of thioctic acid were added and mixed. After the reaction was completed, the pH was adjusted to neutral, and the mixture was dialyzed to remove impurities and dried to obtain thioctic acid modified hyaluronic acid.

4. The preparation method according to claim 3, characterized in that, In S1, the molar ratio of N,N'-carbonyl imidazole to lipoic acid is 1:1; in S2, the molar ratio of hyaluronic acid: lipoic acid imidazole ester: catalyst is 1:1-3:1, and the catalyst is 4-dimethylaminopyridine.

5. A HALA / GelMA-exosome biogel prepared by any one of the preparation methods described in claims 1-4.

6. The application of the HALA / GelMA-exosome bioglue as described in claim 5 in the preparation of lens implantation adhesive.